2022
DOI: 10.3390/polym14235319
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improved Wettability of Polyetheretherketone (PEEK) Polymers by Non-Equilibrium Plasma Treatment

Abstract: Polyetheretherketone (PEEK) is the material of choice in several applications ranging from the automotive industry to medicine, but the surface properties are usually not adequate. A standard method for tailoring surface properties is the application of gaseous plasma. The surface finish depends enormously on the processing parameters. This article presents a review of strategies adapted for improved wettability and adhesion of PEEK. The kinetics of positively charged ions, neutral reactive plasma species, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…DPNS is a technique which although creates surface changes in the polymer material, keeps intact the bulk properties which gives it an advantage over the biological interaction with the surface of implants. The XRD analysis obtained showed similar diffraction patterns for all samples (Figure B), which proves that the bulk chemical structure was not damaged or modified, confirming the stability of bulk properties of PEEK even after DPNS plasma treatment. Further investigation of the XRD peaks, as shown in Table , quantified changes in the area of each peak and provided the corresponding full width at half-maximum (fwhm) intensity and the crystal thickness (CT). Although a similar chemical structure was observed in the three PEEK samples, a grazing angle was applied to determine small chemical differences at the surface, which showed the chemistry changes at a specific peak due to the Ar + ion irradiation.…”
Section: Results and Discusionmentioning
confidence: 52%
See 1 more Smart Citation
“…DPNS is a technique which although creates surface changes in the polymer material, keeps intact the bulk properties which gives it an advantage over the biological interaction with the surface of implants. The XRD analysis obtained showed similar diffraction patterns for all samples (Figure B), which proves that the bulk chemical structure was not damaged or modified, confirming the stability of bulk properties of PEEK even after DPNS plasma treatment. Further investigation of the XRD peaks, as shown in Table , quantified changes in the area of each peak and provided the corresponding full width at half-maximum (fwhm) intensity and the crystal thickness (CT). Although a similar chemical structure was observed in the three PEEK samples, a grazing angle was applied to determine small chemical differences at the surface, which showed the chemistry changes at a specific peak due to the Ar + ion irradiation.…”
Section: Results and Discusionmentioning
confidence: 52%
“…This also provided information on changes in crystal structure and thickness due to DPNS treatment, by only varying fluence parameter, on the modified PEEK nanosurface. The XRD peaks showed the main peaks at 18.8, 20.8, 22.8, and 28.9° are presented in all samples, and correspond to the PEEK crystal planes [110], [111], [200], and [211], respectively. …”
Section: Results and Discusionmentioning
confidence: 99%
“…Figure 6b Here, it is worth mentioning that Botel et al [37] reported immeasurably low WCA on PEEK samples after treating them with capacitively coupled oxygen plasma for a few minutes, but the selected samples were rough because they were sand-blasted before the plasma treatment. Other authors reported rather inadequate wettability of this polymer after treatment with oxygen plasma, indicating that a WCA of approximately 10 • is not trivial to achieve when treating PEEK in the glowing plasma [38].…”
Section: Resultsmentioning
confidence: 94%
“…Twenty-four grades of milled, PAEK powders were supplied by Victrex [24] including PEEK, PEK and PEEK-PEDEK copolymer grades. PEEK-PEDEK grades are referred to as PDK in the rest of the paper.…”
Section: Methodsmentioning
confidence: 99%